Preparation method of monatomic catalyst modified cyclodextrin derived carbon coated lithium manganese iron phosphate composite electrode material

By synergistically modifying lithium manganese iron phosphate materials with cyclodextrin-derived three-dimensional carbon layers and transition metal single-atom modifications, the conductivity and manganese leaching problems were solved, thereby improving the electrochemical performance and lifespan of lithium-ion batteries.

CN120841476APending Publication Date: 2025-10-28HUBEI XINGFA CHEM GRP CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202511018732.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-07-23
Publication Date
2025-10-28

AI Technical Summary

Technical Problem

Existing lithium manganese iron phosphate materials suffer from poor conductivity, narrow lithium-ion diffusion paths, manganese leaching, and battery polarization, resulting in insufficient utilization of active materials and poor battery performance.

Method used

By employing cyclodextrin-derived three-dimensional carbon layers and transition metal single atoms for synergistic modification, a three-dimensional porous conductive network is formed on the surface of lithium manganese iron phosphate, and metal single atoms such as Co and Ni are anchored on it to form a continuous active interface, thereby improving electron and ion transport performance.

Benefits of technology

It significantly improves the electronic conductivity and lithium-ion transport efficiency of the material, suppresses manganese leaching, improves the cycle stability and rate performance of the battery, and reduces production costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120841476A_ABST
    Figure CN120841476A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of lithium batteries, and provides a preparation method of a monatomic catalyst modified cyclodextrin derived carbon coated lithium manganese iron phosphate composite electrode material, which comprises the following steps: preparing monatomic catalyst modified cyclodextrin; preparing precursor slurry; preparing precursor particles; and preparing the monatomic catalyst modified cyclodextrin derived carbon coated lithium manganese iron phosphate composite electrode material. The cyclodextrin derived carbon used as a coating material is used as a carbon coating raw material, so that uniform coating of the surface of the lithium manganese iron phosphate positive electrode material can be realized, a three-dimensional conductive network with a porous network can be constructed, the electronic conductivity of the material is remarkably improved, and meanwhile, the phenomenon that a compact nonporous structure is easily formed after pyrolysis of a traditional carbon source is avoided; the lithium ion transmission path is reduced, and the ion transmission efficiency is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of lithium battery technology, specifically relating to a method for preparing a cyclodextrin-derived carbon-coated lithium manganese iron phosphate composite electrode material modified with a single-atom catalyst. Background Art

[0002] Lithium-ion batteries (LIBs) have become the core power source for electric vehicles, energy storage power stations, and portable electronic devices due to their pollution-free, high energy density, and long cycle life. As a key component of the battery, the performance of the cathode material directly affects the battery's energy output and durability. In recent years, lithium manganese iron phosphate (LiMn) has become increasingly popular. x Fe (1-x) PO4 (LMFP) is considered an ideal candidate material that combines the safety of lithium iron phosphate (LFP) with the high energy density of ternary materials due to its high voltage platform (~4.1V), excellent low temperature performance (capacity retention >75% at -20℃) and cost advantages.

[0003] Lithium manganese iron phosphate (LMFP) and lithium iron phosphate (LFP) have the same theoretical capacity, but LMFP has a higher operating voltage, which increases with increasing manganese content. Similar to LFP, LMFP has a stable olivine structure and releases very little oxygen during high-temperature charge / discharge, thus exhibiting high safety performance. However, LMFP materials have a large bandgap and narrow lithium-ion diffusion paths, resulting in poor charge transport performance, leading to insufficient utilization of active materials and poor rate performance. Furthermore, the Jahn-Teller effect and manganese dissolution during charge / discharge increase battery polarization and accelerate capacity decay.

[0004] Although a patent (CN117913227A) proposes to coat LMFP materials with a composite carbon source using inorganic and multiple organic carbon sources, achieving a relatively uniform carbon coating layer and effectively improving the conductivity of LMFP, the dense carbon coating layer undoubtedly increases the lithium-ion transport path. Other approaches (such as CN116169262A) dope the carbon coating layer with metal single atoms to improve conductivity and lithium-ion migration rate, but single atoms cannot fully utilize the interfacial catalytic properties in a two-dimensional carbon layer. Summary of the Invention

[0005] To address the aforementioned problems, this invention provides a method for preparing a cyclodextrin-derived carbon-coated lithium manganese iron phosphate composite electrode material modified with a single-atom catalyst. It proposes an innovative scheme for the synergistic modification of a cyclodextrin-derived three-dimensional carbon layer and a single-atom transition metal. Through dual optimization of material structure design and interface engineering, it overcomes the technical contradiction of the difficulty in synergistically improving the conductivity of LMFP and inhibiting manganese dissolution, providing an efficient and economical solution for achieving high energy density and long cycle life lithium-ion batteries.

[0006] This invention provides a method for preparing a cyclodextrin-derived carbon-coated lithium manganese iron phosphate composite electrode material modified with a single-atom catalyst, comprising the following steps: (1) Dissolve cyclodextrin and carbon source in metal salt solution, stir continuously to disperse, and then heat to evaporate water to form gel; (2) Weigh the lithium source, iron source, manganese source and gel according to the stoichiometric ratio of the elements in the lithium manganese iron phosphate to be prepared and add deionized water to mix and prepare a mixed slurry. After mixing evenly, grind to obtain a precursor slurry with a suitable particle size. (3) The precursor slurry is stirred at a constant speed and then spray-dried to obtain lithium manganese iron phosphate precursor particles. (4) The lithium manganese iron phosphate precursor particles are sintered in H2 / Ar and then crushed to obtain a cyclodextrin-derived carbon-coated lithium manganese iron phosphate composite electrode material modified with a single atom catalyst.

[0007] In step (1), the carbon source includes any one or more of glucose, polyethylene glycol or sucrose, and the amount added accounts for 8-15 wt% of the total mass of the raw materials.

[0008] In step (1), the cyclodextrin includes any one or more of α-cyclodextrin, β-cyclodextrin or γ-cyclodextrin, and the amount added accounts for 2-5 wt% of the total mass of the raw materials.

[0009] In step (1), the metal salt is any one or more of cobalt nitrate, nickel chloride, or ruthenium chloride, and the amount added accounts for 0.1-1 wt% of the total mass of the raw materials.

[0010] Preferred manganese sources include any one or more of manganese sulfate, manganese oxalate, or manganese carbonate; iron sources include any one or more of ferric oxide, iron powder, ferric phosphate, ferric nitrate, or ferric lactate; lithium sources include any one or more of lithium carbonate, lithium nitrate, lithium phosphate, or lithium hydroxide; and phosphorus sources include any one or more of phosphoric acid, ammonium dihydrogen phosphate, or diammonium hydrogen phosphate.

[0011] The preferred molar ratio of manganese in the manganese source, iron in the iron source, lithium in the lithium source, and phosphorus in the phosphorus source is 0.8-0.2:0.2-0.8:1:1; the preferred molar ratio of manganese in the manganese source, iron in the iron source, lithium in the lithium source, and phosphorus in the phosphorus source is 0.3:0.7:1:1. The preferred mass ratio of the total mass of the manganese, iron, lithium, and phosphorus sources to the total mass of the carbon source is 100:5-15; the preferred mass ratio of the total mass of the manganese, iron, lithium, and phosphorus sources to the total mass of the cyclodextrin is 100:5.

[0012] In step (2), a dopant is also added, which is any one or more of magnesium oxide, titanium dioxide, or ammonium metavanadate. The dopant accounts for 1-5 wt% of the total mass of the raw materials.

[0013] The preferred precursor slurry particle size D in step (2) 50 The wavelength is 200-400 nm, preferably 250-300 nm.

[0014] In step (3), the preferred spray drying outlet temperature is 75-90℃.

[0015] The sintering temperature in step (4) is 500-850℃, and the holding time is 4-9 h. The preferred sintering temperature is 750℃, and the holding time is 8 h.

[0016] The method for preparing cyclodextrin-derived carbon-coated lithium manganese iron phosphate composite electrode materials modified with single-atom catalysts proposed in this invention has the following advantages compared with existing technologies: 1. The cyclodextrin used in the above method has a conical hollow cylindrical three-dimensional ring structure. After pyrolysis, it can form a three-dimensional porous conductive network in situ on the surface of lithium manganese iron phosphate material. This not only improves the electron / ion transport efficiency, but also acts as a physical barrier to reduce the erosion of the active material by the electrolyte. While significantly improving the electronic conductivity of the material, it avoids the formation of a dense, non-porous structure after the pyrolysis of traditional carbon sources, which reduces the lithium ion transport path and improves the ion transport efficiency.

[0017] 2. Modification is achieved by anchoring Co and Ni single-atom metals to the surface of a cyclodextrin-derived carbon coating layer, replacing noble metal nanoparticles (Pt, Au), thereby reducing material production costs and particle agglomeration issues. Furthermore, Mn is modulated through d-π electron interactions. 3+ Electron-occupied states and adsorption of Mn 2+ It suppresses Jahn-Teller distortion and manganese dissolution, significantly improving the electron transport performance of composite materials.

[0018] 3. The three-dimensional conductive network ensures uniform dispersion of single atoms, forming a continuous active interface; single atoms endow the three-dimensional conductive network interface with catalytic effect and further improve the charge transport performance of the composite material. The synergistic effect of the two significantly improves the cycle stability and rate performance of lithium manganese iron phosphate materials. Attached Figure Description

[0019] Figure 1 The image shows the XRD pattern of the cyclodextrin-derived carbon-coated lithium manganese iron phosphate composite electrode material modified with a single-atom catalyst prepared in Example 1.

[0020] Figure 2The image shows a SEM image of the cyclodextrin-derived carbon-coated lithium manganese iron phosphate composite electrode material modified with a single-atom catalyst prepared in Example 1.

[0021] Figure 3 The image shows a HAADF-STEM image of the single-atom catalyst-modified cyclodextrin-derived carbon-coated lithium manganese iron phosphate composite electrode material prepared in Example 1.

[0022] Figure 4 The graph shows the charge-discharge performance test results of the lithium manganese iron phosphate prepared in Example 1. Detailed Implementation

[0023] The endpoints and any values ​​of the ranges disclosed in this invention are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of the various ranges, the endpoint values ​​of the various ranges and individual point values, and individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this invention.

[0024] Example 1 A method for preparing a cyclodextrin-derived carbon-coated lithium manganese iron phosphate composite electrode material modified with a single-atom catalyst includes the following steps: (1) Dissolve 1.25g β-cyclodextrin, 3.85g glucose and 0.215g cobalt nitrate in pure water, stir continuously to disperse, and then heat to evaporate water to form a gel.

[0025] (2) Weigh 8.577g manganese oxalate, 9.674g iron phosphate, 6.896g lithium nitrate, 9.800g phosphoric acid and all the gel as raw materials, add deionized water and mix to make a mixed slurry. The slurry is ground in a sand mill at 2500rpm until the precursor slurry particle size D50 is 320 nm to obtain a precursor slurry with a suitable particle size.

[0026] (3) The precursor slurry is stirred at a constant speed and then spray-dried to obtain lithium manganese iron phosphate precursor particles. The outlet air temperature of the spray dryer is controlled at 85°C.

[0027] (4) The lithium manganese iron phosphate precursor particles were sintered at 700°C for 9 h in a mixed atmosphere of H2 / Ar and then crushed to obtain a cobalt atom catalyst-modified cyclodextrin-derived carbon-coated lithium manganese iron phosphate composite electrode material.

[0028] Example 2 The method and steps are the same as in Example 1, except that the cobalt nitrate solution is replaced with nickel chloride. The final product is a nickel atom catalyst-modified cyclodextrin-derived carbon-coated lithium manganese iron phosphate composite electrode material.

[0029] Example 3 The method and steps are the same as in Example 1, except that the cobalt nitrate solution is replaced with ruthenium chloride. The final product is a ruthenium atom catalyst-modified cyclodextrin-derived carbon-coated lithium manganese iron phosphate composite electrode material.

[0030] Example 4 The method and steps are the same as in Example 1, except that no metal salt is included. The final product is a carbon-coated lithium manganese iron phosphate composite electrode material.

[0031] Comparative Example The method and steps are the same as in Example 1, but without metal salts and cyclodextrin. The final product is a carbon-coated lithium manganese iron phosphate composite electrode material.

[0032] The metal single-atom content, specific surface area, powder compaction density, and electrical properties of the composite materials prepared in each embodiment were tested, and the test results are shown in Table 1 below: Table 1

[0033] The above embodiments are merely illustrative examples and are not intended to limit the implementation. Those skilled in the art will recognize that other variations or modifications can be made based on the above description. It is neither necessary nor possible to exhaustively list all possible implementations; therefore, any obvious variations or modifications derived therefrom remain within the scope of protection of this invention.

Claims

1. A method for preparing a cyclodextrin-derived carbon-coated lithium manganese iron phosphate composite electrode material modified with a single-atom catalyst, characterized in that, Includes the following steps: (1) Dissolve cyclodextrin and carbon source in metal salt solution, stir continuously to disperse, and then heat to evaporate water to form gel; (2) Weigh the lithium source, iron source, manganese source and gel according to the stoichiometric ratio of the elements in the lithium manganese iron phosphate to be prepared and add deionized water to mix and prepare a mixed slurry. After mixing evenly, grind to obtain a precursor slurry with a suitable particle size. (3) The precursor slurry is stirred at a constant speed and then spray-dried to obtain lithium manganese iron phosphate precursor particles. (4) The lithium manganese iron phosphate precursor particles are sintered in a mixed atmosphere of H2 / Ar and then crushed to obtain a cyclodextrin-derived carbon-coated lithium manganese iron phosphate composite electrode material modified with a single atom catalyst.

2. The preparation method of the cyclodextrin-derived carbon-coated lithium manganese iron phosphate composite electrode material modified with a single-atom catalyst as described in claim 1, characterized in that: In step (1), the cyclodextrin includes any one or more of α-cyclodextrin, β-cyclodextrin or γ-cyclodextrin, and the amount added accounts for 2-5 wt% of the total mass of the raw materials.

3. The preparation method of the cyclodextrin-derived carbon-coated lithium manganese iron phosphate composite electrode material modified with a single-atom catalyst as described in claim 1, characterized in that: In step (1), the metal salt is any one or more of cobalt nitrate, nickel chloride, or ruthenium chloride, and the amount added accounts for 0.1-1 wt% of the total mass of the raw materials.

4. The preparation method of the cyclodextrin-derived carbon-coated lithium manganese iron phosphate composite electrode material modified with a single-atom catalyst as described in claim 1, characterized in that: In step (1), the carbon source includes any one or more of glucose, polyethylene glycol or sucrose, and the amount added accounts for 8-10 wt% of the total mass of the raw materials.

5. The preparation method of the cyclodextrin-derived carbon-coated lithium manganese iron phosphate composite electrode material modified with a single-atom catalyst as described in claim 1, characterized in that: In step (2), the manganese source includes any one or more of manganese sulfate, manganese oxalate, or manganese carbonate; the iron source includes any one or more of ferric oxide, iron powder, ferric phosphate, ferric nitrate, or ferric lactate; the lithium source includes any one or more of lithium carbonate, lithium nitrate, lithium phosphate, or lithium hydroxide; the phosphorus source includes any one or more of phosphoric acid, ammonium dihydrogen phosphate, or diammonium hydrogen phosphate; and the carbon source is any one or more of glucose, polyethylene glycol, sucrose, or starch.

6. The preparation method of the cyclodextrin-derived carbon-coated lithium manganese iron phosphate composite electrode material modified with a single-atom catalyst as described in claim 1, characterized in that: In step (2), a dopant is also added, wherein the dopant is any one or more of magnesium oxide, titanium dioxide or ammonium metavanadate.

7. The preparation method of the cyclodextrin-derived carbon-coated lithium manganese iron phosphate composite electrode material modified with a single-atom catalyst as described in claim 6, characterized in that: In step (2), the molar ratio of manganese in the manganese source, iron in the iron source, lithium in the lithium source, and phosphorus in the phosphorus source is 0.8-0.2:0.2-0.8:1:1; the dopant accounts for 1-5 wt% of the total mass of the raw materials; and the carbon source accounts for 8-10 wt% of the total mass of the raw materials.

8. The preparation method of the cyclodextrin-derived carbon-coated lithium manganese iron phosphate composite electrode material modified with a single-atom catalyst as described in claim 1, characterized in that: In step (2), the precursor slurry particle size D 50 The wavelength is 250-400 nm.

9. The preparation method of the cyclodextrin-derived carbon-coated lithium manganese iron phosphate composite electrode material modified with a single-atom catalyst as described in claim 1, characterized in that: In step (3), the outlet air temperature of the spray dryer is 75-90℃.

10. The preparation method of the cyclodextrin-derived carbon-coated lithium manganese iron phosphate composite electrode material modified with a single-atom catalyst as described in claim 1, characterized in that: In step (4), the sintering temperature is 500-850℃ and the holding time is 4-9h.

Citation Information

Patent Citations

  • Composite carbon coated lithium manganese iron phosphate material and preparation method thereof

    CN117913227A

  • Preparation method of carbon coated lithium manganese iron phosphate

    CN107768613A

  • Cyclodextrin-based transition metal monatomic catalytic material and preparation method thereof

    CN110801863A

  • Carbon-coated lithium manganese iron phosphate material, preparation method thereof and battery

    CN115744860A

  • Monatomic doped lithium manganese iron phosphate composite material and preparation method and application thereof

    CN116169262A